Dual role of mesenchymal stem/stromal cells and their cell‐free extracellular vesicles in colorectal cancer - Saadh, Mohamed J.; Mohamed, Asma'a H.; Almoyad, Muhammad Ali Abdullah; Allela, Omer Qutaiba B.; Amin, Ali H.; Malquisto, April Ann; Wong, Tze Jin; Sârbu, Ioan; AlShamsi, Faisal; Elsaid, Fahmy Gad; Akhavan-Sigari, Reza (John Wiley and Sons Ltd, 2024)
Colorectal cancer (CRC) is one of the main causes of cancer‐related deaths. However, the surgical control of the CRC progression is difficult, and in most cases, the metastasis leads to cancer‐related mortality. Mesenchymal stem/stromal cells (MSCs) with potential translational applications in regenerative medicine have been widely researched for several years. MSCs could affect tumor development through secreting exosomes. The beneficial properties of stem cells are attributed to their cell–cell interactions as well as the secretion of paracrine factors in the tissue microenvironment. For several years, exosomes have been used as a cell‐free therapy to regulate the fate of tumor cells in a tumor microenvironment. This review discusses the recent advances and current understanding of assessing MSC‐derived exosomes for possible cell‐free therapy in CRC.